2019
DOI: 10.1055/s-0037-1611643
|View full text |Cite
|
Sign up to set email alerts
|

Kinetically Controlled Fischer Glycosidation under Flow Conditions: A New Method for Preparing Furanosides

Abstract: Kinetically controlled Fischer glycosidation was achieved under flow conditions. β-Hydroxy-substituted sulfonic acid functionalized silica (HO-SAS) was used as an acid catalyst. This reaction directly converted aldohexoses into kinetically favored furanosides to enable the practical synthesis of furanosides. After optimization of the reaction temperature and residence time, glucofuranosides, galactofuranosides, and mannofuranosides were synthesized in good yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…The PEM reactor features many characteristics designed to overcome the disadvantages of conventional electrosynthetic processes, such as the necessity of supporting electrolytes. Moreover, because the PEM reactor is a flow reactor (Masui et al, 2019;Ashikari et al, 2020;Colella et al, 2020;Harenberg et al, 2020;Ichinari et al, 2020;Otake et al, 2020;Saito and Kobayashi, 2020;Watanabe et al, 2020;Ahn et al, 2021;Prieschl et al, 2021;Sivo et al, 2021), it offers numerous advantages, including precise control of the reaction time, the applicability of successive reactions, and scalability, which are rarely applicable in batch electrosynthesis (Elsherbini and Wirth, 2019;Noël et al, 2019;Hu et al, 2020). Therefore, various applications of PEM reactor systems utilizing electrosynthetic processes, such as the reduction of toluenes (Takano et al, 2016;Fukazawa et al, 2018) and alkenes (Ogumi et al, 1981), and asymmetric hydrogenation of α,β-unsaturated acids (Fukazawa et al, 2020), have been reported (Raoult et al, 1984;Jorissen, 1996;Kishi et al, 2020;Fukazawa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The PEM reactor features many characteristics designed to overcome the disadvantages of conventional electrosynthetic processes, such as the necessity of supporting electrolytes. Moreover, because the PEM reactor is a flow reactor (Masui et al, 2019;Ashikari et al, 2020;Colella et al, 2020;Harenberg et al, 2020;Ichinari et al, 2020;Otake et al, 2020;Saito and Kobayashi, 2020;Watanabe et al, 2020;Ahn et al, 2021;Prieschl et al, 2021;Sivo et al, 2021), it offers numerous advantages, including precise control of the reaction time, the applicability of successive reactions, and scalability, which are rarely applicable in batch electrosynthesis (Elsherbini and Wirth, 2019;Noël et al, 2019;Hu et al, 2020). Therefore, various applications of PEM reactor systems utilizing electrosynthetic processes, such as the reduction of toluenes (Takano et al, 2016;Fukazawa et al, 2018) and alkenes (Ogumi et al, 1981), and asymmetric hydrogenation of α,β-unsaturated acids (Fukazawa et al, 2020), have been reported (Raoult et al, 1984;Jorissen, 1996;Kishi et al, 2020;Fukazawa et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…45,58 These two isomers were reported to be the kinetically favored products formed in the initial stage of the acid-catalyzed Fischer glycosidation of glucose and could be further transformed into thermodynamically more stable MDGP as the dominant glycosidation product (Scheme 3). 59,60 Thus, NMR data indicated the occurrence of furanoside formation via the reversed ring-contraction reaction of pyranosides. As the furanoside-to-pyranoside conversion proceeds via a chain-form intermediate, namely D-glucose dimethyl acetal (GDMA), 61 it is reasonable that the reverse process also proceeds via GDMA, which contributes to the peak at 76.3 ppm.…”
Section: Intermediates Formed During Methanolysismentioning
confidence: 99%
“…For mannose, the optimal conditions were found to be 100 °C with residence time of 30 s, resulting in a yield of 67% with an α:β ratio of 76:24. The optimal residence time for galactose was found to be much higher at 15 min with a temperature of 60 °C, resulting in 86% yield with an α:β ratio of 26:74 [ 57 ].…”
Section: Fischer Glycosylation In Reactorsmentioning
confidence: 99%